Pelatihan Pembuatan Media Pembelajaran Digital Animals Education Berbasis Powert Point Untuk Mengembangkan Inovasi Guru Di SDN 16 Cakranegara - Muhammad Sobri; Asri Fauzi; Lalu Wira Zain Amrullah; Aisa Nikmah Rahmatih; Setiani Novitasari (DEDIKASI : Jurnal Pengabdian Kepada Masyarakat, 2025)
Advancements in technology necessitate that teachers engage in continuous innovation to develop interactive and engaging learning media. However, SDN 16 Cakranegara has encountered challenges in producing learning media in the form of PowerPoint presentations. These difficulties stem primarily from the limited dissemination of knowledge and inadequate training related to the development of PowerPoint-based instructional media. Consequently, this situation poses a significant challenge in enhancing teachers’ competencies in utilizing technology as an effective instructional tool. The purpose of this training program is to support teachers in designing digital learning media entitled Animals Education, developed through PowerPoint, with the aim of fostering students’ interest in learning and enriching their overall learning experiences. Specifically, the objectives of the training are to: (1) equip teachers with technical skills in employing PowerPoint to design interactive instructional media; (2) encourage creativity among teachers in developing innovative pedagogical practices aligned with students’ learning needs; and (3) enhance the quality of instruction through the integration of relevant and engaging digital media.The implementation process consists of several stages, namely dissemination, training, technology application, mentoring, evaluation, and sustainability efforts. It is anticipated that this program will strengthen teachers’ capacity to create more innovative, engaging, and contextually relevant learning experiences in the era of digitalization.The expected output of this community engagement activity is a scholarly article published in an ISSN-accredited journal, Wartadesa (https://jwd.unram.ac.id/index.php/jwd). Additionally, the training is expected to produce a tangible product in the form of digital learning media developed using PowerPoint.